JUVENILE SEXUAL OFFENDER: PSCYHOLOGICAL ABUSE BY PARENTS OR CAREGIVER AND ISLAMIC PERSPECTIVES - Adira Rizki Shabrina; Karimulloh Karimulloh; Zulfa Febriani (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2021)
Psychological abuse has been attributed as the root cause of sexual violence by juvenile, or known as juvenile sexual offender (JSO), while research related to the topic is still little. The purpose of this study is to understand the dynamics of psychological abuse by parents or caregivers so that it is assumed to be a trigger for sexual violence by juvenile, and to see the Islamic views of it. This study used qualitative method with a phenomenological and descriptive approach. The results showed that there were three main themes identified, namely: psychological abuse, appreciation of psychological abuse and the meaning of sexual relations. It can be concluded that participants who feel that they did not get affection from their parents or caregiver as a result of the psychological abuse they experienced are encouraged to seek affection through sexual intercourse. Based on Islamic perspective, psychological abuse by parents or caregivers is a form of violation of the mandate that Allah SWT has entrusted to them.